Reducing Perfectionism and Enhancing Self-Worth: The Role of Self-Efficacy Training in Gifted Adolescents - Ghasemi, Mohammadreza; Nejatifar, Sara (Psychological Research in Individuals with Exceptional Needs, 2024)
This study aimed to evaluate the effectiveness of self-efficacy training in reducing perfectionism and enhancing self-worth among gifted high school students. A randomized controlled trial design was employed with 40 gifted high school students randomly assigned to either an intervention group (n = 20) or a control group (n = 20). The intervention group participated in an eight-session self-efficacy training program, while the control group received no intervention. Both groups were assessed at baseline, immediately post-intervention, and at a four-month follow-up. Perfectionism and self-worth were measured using validated scales. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests. The intervention group showed a significant reduction in perfectionism scores from baseline (M = 72.45, SD = 5.28) to post-intervention (M = 64.32, SD = 6.15) and follow-up (M = 66.89, SD = 5.92) compared to the control group, which showed no significant change. Similarly, self-worth scores in the intervention group increased significantly from baseline (M = 32.19, SD = 4.15) to post-intervention (M = 38.45, SD = 3.92) and follow-up (M = 36.98, SD = 4.20), whereas the control group showed no significant change. The ANOVA results indicated significant main effects of time (F(2, 76) = 27.12, p < .001) and group (F(1, 76) = 102.95, p < .001) for perfectionism, and time (F(2, 76) = 24.65, p < .001) and group (F(1, 76) = 111.30, p < .001) for self-worth, with significant interaction effects for both variables. Self-efficacy training is effective in reducing perfectionism and enhancing self-worth among gifted high school students. The positive effects were maintained at a four-month follow-up, suggesting the potential long-term benefits of such interventions in this population.